Paleoradiology of the Savoca Mummies, Sicily, Italy (18th–19th Centuries AD). Issue 6 (June 2015) - Piombino‐Mascali, Dario; Jankauskas, Rimantas; Zink, Albert R.; Sergio Todesco, M.; Aufderheide, Arthur C.; Panzer, Stephanie
ABSTRACT Mummified remains have been successfully studied radiologically since the end of the 19th century, giving rise to a specific field of research—paleoradiology. In this paper, we present the results of the first radiological investigation of a collection of Sicilian mummies found in a subterranean chamber beneath the Capuchin Church of Savoca. The chamber contains a number of preserved bodies, either held in special niches in the walls or interred within coffins. A recent detailed radiological examination of these mummies allowed the authors to determine information relating to the funerary treatment and some of the pathological alterations witnessed in the remains. Specifically, evidence of gout and DISH was identified, along with frequent degenerative joint disease, suggestive of rich dietary habits and a longer life expectancy. These findings were interpreted in the light of historical information and the social status of the subjects concerned. Anat Rec, 298:988–1000, 2015. © 2015 Wiley Periodicals, Inc.